A high-hydrophilic-anti-fouling MOFs sponge uranium extraction adsorption material and a preparation method thereof
Patent Information
- Application Number
- CN202311137001.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-05
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-09-05
AI Technical Summary
Existing metal-organic framework (MOF) materials are susceptible to marine fouling and biocorrosion in the field of uranium extraction from seawater, which reduces their adsorption performance. Furthermore, traditional antifouling agents are toxic to the marine environment, limiting their application.
Highly hydrophilic and antifouling MOF sponge materials were prepared by pretreating the sponge matrix with chitosan and phytic acid covalent crosslinking. The phosphate-amide functionalized sponge was then reacted with the MOF precursor for in-situ nucleation growth to form a metal-organic framework-coated sponge material.
It achieves the inhibition of marine fouling organisms, improves the hydrophilicity and adsorption capacity of the material, reduces economic costs, and is easy to separate and recycle, making it suitable for seawater uranium extraction processes.
Smart Images

Figure CN117299092B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of functional materials technology, specifically a highly hydrophilic and antifouling MOF sponge uranium extraction adsorbent material and its preparation method. Background Technology
[0002] Nuclear energy, as a clean and low-carbon energy source, has become a major energy source for future social development. Uranium, as a key radioactive raw material in nuclear energy resources, is a crucial guarantee for the sustainable development of nuclear energy. Given the limited nature of terrestrial uranium resources, the development of unconventional uranium resources is urgently needed. The ocean contains abundant uranium resources, with total reserves more than 1000 times that of terrestrial uranium mines. Compared to the environmental hazards caused by traditional uranium mining, such as the generation of large amounts of radioactive wastewater and dust, seawater uranium extraction technology has advantages such as low pollution, simple process, and high product purity. Adsorption methods are considered ideal for seawater uranium extraction due to their low cost, high extraction rate, and ease of continuous operation. Inorganic-organic composite materials, due to their low cost and high stability, have become commonly used adsorption materials. Among them, metal-organic frameworks (MOFs) are novel porous materials formed by hybridization of metal ions and organic ligands. They possess a micro-nano scale framework-type regular pore structure, ultra-large specific surface area and porosity, and low solid density, showing potential application prospects in the field of seawater uranium extraction. However, most metal-organic frameworks (MOFs) are powder materials, which are not easy to recover and separate after adsorption saturation. More importantly, the complex marine environment contains a large number of marine fouling organisms, which can accelerate the corrosion and degradation of the adsorbent structure, reduce the performance of the material, and the fouling organisms are tough and can easily adhere to the surface of the adsorbent, which will reduce the interaction between the adsorbent and seawater during the adsorption process, reduce the adsorbent's adsorption capacity, and seriously limit the development of adsorbent materials in the field of seawater uranium extraction.
[0003] Existing marine antifouling methods generally involve mechanical, physical, chemical, biological, and ecological fields. The basic principles of antifouling include inhibition of attachment, inhibition of growth, and toxicity. Currently, commercially available antifouling agents are mainly copper-containing inorganic compounds that exert their biotoxic effects by inhibiting cell activity; these are primarily cuprous oxide and cuprous thiocyanate. However, copper ions also exhibit some toxicity to marine organisms and can damage the marine environment.
[0004] Therefore, developing uranium extraction materials with antifouling properties is the main development direction for uranium extraction adsorbents, while protecting the marine ecological environment. Summary of the Invention
[0005] Objective of the invention: This invention provides a highly hydrophilic and antifouling MOF sponge uranium extraction adsorbent material and its preparation method. After pretreating the surface of the sponge matrix pores with special chitosan and phytic acid covalent crosslinking, the pretreated phosphate-amide functionalized sponge is reacted with MOF precursors in sequence for in-situ nucleation growth, thus obtaining a metal-organic framework-coated sponge material, namely a highly hydrophilic and antifouling MOF sponge adsorbent material.
[0006] Technical solution: A method for preparing a highly hydrophilic and antifouling MOF sponge-type uranium extraction adsorbent material, comprising the following steps:
[0007] Step 1: Select melamine sponge or polyurethane sponge as the sponge matrix, clean and dry it before use;
[0008] Step 2: Prepare the phosphate-amide functionalized sponge matrix. The specific steps are as follows:
[0009] Phytic acid was added to chitosan acetate solution and mixed evenly to obtain a mixed solution; the cleaned and dried sponge matrix was immersed in the mixed solution to completely wet the sponge matrix; glutaraldehyde was then added to the mixed solution, and after reacting for a period of time, the sponge matrix was removed, washed, and freeze-dried to obtain a phosphate-amide functionalized sponge matrix.
[0010] Step 3: Prepare highly hydrophilic and antifouling MOF sponge uranium extraction adsorbent material. The specific operations are as follows:
[0011] MOF precursor solutions, central metal ion solution, and ligand solution were prepared separately. The phosphate-amide functionalized sponge matrix was immersed in the central metal ion solution and completely wetted. The matrix was then stirred at room temperature for a period of time. The ligand solution was then added to the central metal ion solution and stirred for a period of time. After removing the sponge matrix, cleaning and drying were performed to obtain a highly hydrophilic and antifouling sponge-based uranium extraction adsorbent.
[0012] Preferably, in step one, the cleaning conditions are: using deionized water and anhydrous ethanol two to three times in sequence; the drying conditions are: drying at 60°C.
[0013] Preferably, step two, preparing the phosphate-amide functionalized sponge matrix, is carried out as follows:
[0014] In step (1), phytic acid is added to the chitosan acetate solution and mixed evenly to obtain a mixed solution. The chitosan acetate solution contains 0.5-2% chitosan by mass, and the mass ratio of phytic acid to chitosan is 1:(0.5-2).
[0015] Step (2): Immerse the cleaned and dried sponge substrate in the mixed solution in step (1), and squeeze-release cycle 3-5 times to completely wet the sponge;
[0016] Step (3): After the sponge matrix is completely wetted, glutaraldehyde is added to the mixed solution. The mass concentration of glutaraldehyde in the mixed solution is 1.5-3%. The reaction is carried out at 60℃ for 4-6 hours. The sponge is taken out and washed three times with deionized water and then freeze-dried for 48 hours to obtain the phosphate-amide functionalized sponge matrix.
[0017] Preferably, in the chitosan acetate solution of step (1), the mass concentration of chitosan is 1%; the mass ratio of phytic acid to chitosan is 1:2.
[0018] Preferably, the specific operation of step three is as follows:
[0019] Step A: Prepare the central metal ion solution and ligand solution of the MOF precursor solution respectively;
[0020] In the MOF precursor solution, the central metal ion solution is a zinc nitrate-methanol solution, and the ligand solution is a 2-methylimidazolium methanol solution.
[0021] Alternatively, the central metal ion solution is a cobalt nitrate-methanol solution, and the ligand solution is a 2-methylimidazolium methanol solution;
[0022] Alternatively, the central metal ion solution: the solute is copper nitrate, and the solvent is N,N-dimethylformamide; the ligand solution: the solute is trimesic acid, and the solvent is N,N-dimethylformamide.
[0023] Step B: Immerse the phosphate-amide functionalized sponge matrix in the central metal ion solution, and completely wet the sponge matrix by squeezing-releasing three times, and stir at room temperature for at least 30 minutes.
[0024] Step C: Add the ligand solution to the central metal ion solution and stir the reaction at 25-150℃ for 3-12 hours.
[0025] Step D: Remove the sponge substrate, wash it 3-5 times with deionized water and anhydrous ethanol respectively, and dry it at 60-100℃ for 12 hours to obtain a highly hydrophilic and antifouling sponge-based uranium extraction adsorption material.
[0026] Preferably, in the MOF precursor solution: the central metal ion solution is a zinc nitrate-methanol solution, prepared by dissolving 1.19 g of zinc nitrate in 24 mL of methanol; the ligand solution is a 2-methylimidazole methanol solution, prepared by dissolving 1.64 g of 2-methylimidazole in 40 mL of methanol.
[0027] Preferably, in the MOF precursor solution: the central metal ion solution is a cobalt nitrate-methanol solution, prepared by dissolving 1.16g of cobalt nitrate in 24mL of methanol; the ligand solution is a 2-methylimidazole methanol solution, prepared by dissolving 1.64g of 2-methylimidazole in 40mL of methanol.
[0028] Preferably, in the MOF precursor solution: the central metal ion solution is prepared by dissolving 0.14 g of copper nitrate in 10 mL of N,N-dimethylformamide; the ligand solution is prepared by dissolving 0.084 g of trimesic acid in 10 mL of N,N-dimethylformamide.
[0029] This invention also provides a method for preparing a highly hydrophilic and antifouling MOFs sponge uranium extraction adsorbent material.
[0030] Beneficial effects:
[0031] 1) The highly hydrophilic and antifouling MOF sponge adsorbent material prepared by this invention is a uranium extraction material that combines marine antifouling and high-efficiency adsorption.
[0032] The highly hydrophilic and antifouling sponge-based uranium extraction adsorbent of this invention has a significant inhibitory effect on the growth of *Nyctaginosa pulvinata*. Phytic acid molecules can significantly improve the overall hydrophilicity of the material, making its water contact angle less than 10°. Under the combined action of chitosan, phytic acid and sponge matrix, the adsorption capacity of MOF sponge can reach more than 160% of that of blank MOF powder when the pH condition is close to that of seawater (≈8.0).
[0033] 2) This invention utilizes a special pretreatment method for the sponge matrix through covalent cross-linking of chitosan and phytic acid, which endows the material with good hydrophilicity and antifouling properties. This not only prevents marine fouling from harming the adsorbent material, but also increases the contact area between seawater and the adsorbent material, facilitating the diffusion of adsorbate into the pores and further improving the adsorption capacity.
[0034] By using covalent cross-linking of chitosan and phytic acid to perform special pretreatment on the sponge matrix, the strong stability and chemical inertness of the sponge matrix itself are overcome. Its surface has abundant nitrogen, phosphorus and oxygen functional groups, which can easily adsorb metal ions, providing sufficient active sites for further nucleation and growth of MOFs on the sponge surface and adsorption of uranium (VI) ions.
[0035] Chitosan, a natural polymer with antimicrobial properties, gives sponge materials significant antifouling properties; phytic acid molecules can significantly improve the overall hydrophilicity of the material, which can not only reduce the coverage of most microorganisms that tend to attach to hydrophobic surfaces, but also increase the contact area between the adsorbent material and seawater, promote the diffusion of adsorbate into the internal pores of the material, and improve the adsorption capacity.
[0036] 3) The preparation process of the highly hydrophilic and antifouling MOFs sponge-based uranium extraction adsorbent material of this invention is simple and easy to operate. The sponge matrix used is melamine or polyurethane sponge, which can effectively reduce economic costs. Melamine sponge and polyurethane sponge are chosen as sponge matrices and porous substrates mainly because their porosity is adjustable, their stability is relatively good, and they are commercially available and relatively inexpensive.
[0037] The adsorption material of this invention utilizes the abundant macropores of a sponge matrix combined with the micro and mesopores of a metal-organic framework material to form an adsorption material with a hierarchical pore structure.
[0038] 4) The highly hydrophilic and antifouling MOFs sponge-based uranium extraction adsorbent of this invention is easy to separate and recycle. The sponge matrix has a rich three-dimensional porous structure and high mechanical strength, which can overcome the problem of difficult separation of traditional MOFs powder adsorbents and facilitate the recycling of adsorbent materials. Attached Figure Description
[0039] Figure 1 This invention compares the seaweed activity of co-cultured with *Rhizophora microcarpa* for different durations with and without Example 1.
[0040] Figure 2 The uranium adsorption capacity of Example 1 of this invention and blank ZIF-8 was added. Detailed Implementation
[0041] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments.
[0042] Example 1
[0043] S1. After washing the melamine sponge two to three times with deionized water and anhydrous ethanol, dry it at a temperature of 60℃ to obtain the washed melamine sponge; the size of the melamine sponge is 2cm×2cm×1cm.
[0044] S2. Phytic acid (PA) is added to the chitosan (CS) acetic acid solution and mixed evenly to obtain a mixed solution. The mass concentration of chitosan in the chitosan acetic acid solution is 1%, and the mass ratio of phytic acid to chitosan is 1:2. The sponge cleaned in S1 is immersed in the above mixed solution and the sponge is completely wetted by the squeeze-release method 3-5 times. Glutaraldehyde is added. The mass concentration of glutaraldehyde in the mixed solution is 1.5%. The reaction is carried out at 60°C for 5 hours. The sponge is taken out and washed three times with deionized water and then freeze-dried for 48 hours to obtain the phosphate-amide functionalized sponge matrix CS / PA.
[0045] The method for preparing chitosan (CS) acetic acid solution is as follows: First, prepare an aqueous acetic acid solution with a mass concentration of 1%, then add chitosan to obtain a chitosan (CS) acetic acid solution with a chitosan mass concentration of 1%.
[0046] S3. Prepare the central metal ion solution and ligand solution of the MOF precursor solution separately; immerse the phosphoric acid-amide functionalized sponge matrix obtained in S2 into a zinc nitrate-methanol solution, and completely immerse the sponge matrix by squeezing-releasing cycle 3 times, stir at room temperature for 30 min (200-400 r / min), then add the ligand solution, and stir at 25℃ for 4 h (200-400 r / min). The resulting sponge is washed 3-5 times with deionized water and anhydrous ethanol and dried at 80℃ for 12 h to obtain the highly hydrophilic and antifouling sponge-based uranium extraction adsorbent CS / PA-ZIF8.
[0047] The central metal ion solution is a zinc nitrate-methanol solution, prepared by dissolving 1.19 g of zinc nitrate in 24 mL of methanol; the ligand solution is a 2-methylimidazole methanol solution, prepared by dissolving 1.64 g of 2-methylimidazole in 40 mL of methanol.
[0048] S4. Performance testing of adsorption materials;
[0049] The adsorbent material obtained in this embodiment is coated with ZIF-8 nanoparticles, which have a water contact angle of <10° and exhibit superhydrophilicity. It showed a significant growth-inhibiting effect when co-cultured with *Nyctaginosa* for 7 days (e.g., ...). Figure 1 The combined effect of the phosphate amide groups and the sponge matrix allows its adsorption capacity to increase by more than 160% at pH levels close to seawater (e.g., Figure 2 After five cycles of adsorption and desorption, the adsorption capacity can be maintained at over 100 mg / g, which is still higher than the adsorption capacity of pure ZIF-8.
[0050] The antifouling performance test procedure is as follows:
[0051] The antifouling performance of *Nyctaginosa microcarpa* was evaluated using it as a model fouling organism. One 0.01g sample from Example 1 was weighed and sterilized under UV light for 2 hours. When the algal cell concentration in the culture medium reached 10... 5 After the cell concentration reached a stable level above 1000 mcg / mL, the sterilized sample from Example 1 was placed in 50 mL of cell culture medium for co-culture. A blank seaweed solution was selected as a control sample. The seaweed solution was observed using an optical microscope at different time points, and the seaweed cell concentration in the corresponding solution was calculated using a hemocytometer. The results are as follows: Figure 1 As shown, compared with the growth trend of blank seaweed, the CS / PA-ZIF8 adsorbent material showed a significant growth inhibition effect when co-cultured with seaweed for 1-7 days.
[0052] The uranium adsorption performance test procedure is as follows:
[0053] Pure ZIF-8 was used as a control sample for uranium adsorption performance. Eight 0.01g portions of the Example 1 sample and the control sample were weighed and placed in conical flasks for uranium adsorption performance testing. 50mL of uranium solution with a pH of 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, and 9.0, and a concentration of 50mg / L, was added to each flask. The flasks were then placed in a constant-temperature shaker and shaken at 150r / min for 12h. The supernatant was collected to determine the uranium concentration. The results are as follows: Figure 2 As shown, at a pH close to seawater (pH 8.0), the adsorption capacity of the CS / PA-ZIF8 adsorbent material can reach 155.6 mg g. -1 This is far higher than the adsorption capacity of pure ZIF-8 (96.3 mg g). -1 ).
[0054] Example 2
[0055] This embodiment is basically the same as the method in Embodiment 1, except that the melamine sponge in S1 is replaced with polyurethane sponge.
[0056] The adsorbent obtained in this embodiment has a slightly different uranium adsorption capacity compared with the adsorbent in Example 1. Under pH 8.0 conditions, after 5 cycles of adsorption and desorption, the adsorption capacity can be maintained at more than 120 mg / g, but it is still higher than the adsorption capacity of pure ZIF-8.
[0057] Example 3
[0058] This embodiment is basically the same as the method in Embodiment 1, except that the chitosan mass concentration in the chitosan acetate solution is 0.5%.
[0059] The adsorbent material obtained in this embodiment was found to have an initial inhibitory effect on the growth of seaweed in the co-culture experiment of *Nyctaginosa pulvinata*. After 5 days of co-culture, the inhibitory effect on seaweed decreased. Under pH 8.0 conditions, the adsorption capacity was still higher than that of pure ZIF-8. Under pH 8.0 conditions, after 5 cycles of adsorption and desorption, the adsorption capacity dropped to about 80 mg / g, which was lower than that of pure ZIF-8.
[0060] Example 4
[0061] This embodiment is basically the same as the method in Embodiment 1, except that the chitosan mass concentration in the chitosan acetate solution is 2%.
[0062] The adsorbent material prepared in this embodiment has a surface water contact angle of <50° and is hydrophilic. The co-culture experiment of *Nyctaginosa pulvinata* confirmed that the adsorbent material has an initial inhibitory effect on the growth of seaweed. After 5 days of co-culture, the inhibitory effect on seaweed decreased. Under pH 8.0 conditions, the adsorption capacity is still higher than that of pure ZIF-8. Under pH 8.0 conditions, after 5 cycles of adsorption and desorption, the adsorption capacity can be maintained at more than 100 mg / g, which is still higher than that of pure ZIF-8.
[0063] Example 5
[0064] This embodiment is basically the same as the method in Embodiment 1, except that the ratio of phytic acid to chitosan added is 1:1.
[0065] The adsorbent material prepared in this embodiment has a surface water contact angle of <10° and is superhydrophilic. The co-culture experiment of *Nyctaginus simonii* confirmed that the adsorbent material has an initial inhibitory effect on the growth of seaweed. After 5 days of co-culture, the inhibitory effect on seaweed decreases. At a pH close to that of seawater, the adsorption capacity can be increased by more than 120%. Under pH 8.0 conditions, after 5 cycles of adsorption and desorption, the adsorption capacity can be maintained at more than 90 mg / g.
[0066] Example 6
[0067] This embodiment is basically the same as the method in Embodiment 1, except that the ratio of phytic acid to chitosan is 2:1.
[0068] The adsorbent material prepared in this embodiment has a surface water contact angle of <10° and is superhydrophilic. The co-culture experiment of *Nyctaginus simonii* confirmed that the adsorbent material has an initial inhibitory effect on the growth of seaweed. After 5 days of co-culture, the inhibitory effect on seaweed decreases. At a pH close to that of seawater, the adsorption capacity can be increased by more than 140%. Under pH 8.0 conditions, after 5 cycles of adsorption and desorption, the adsorption capacity can be maintained at more than 90 mg / g.
[0069] The optimal ratio of phytic acid to chitosan is 1:(0.5-2). The adsorbent material prepared with a ratio of 1:2 has the best effect. Low phytic acid concentration does not significantly improve hydrophilicity, while excessive phytic acid concentration will promote the hydrolysis of chitosan, affecting long-term antifouling performance and cyclic adsorption performance.
[0070] Example 7
[0071] This embodiment is basically the same as the method in Embodiment 1, except that the MOF precursor solution is replaced. In this embodiment, the MOF precursor solution is as follows: the central metal ion solution is a cobalt nitrate-methanol solution, which is prepared by dissolving 1.16g of cobalt nitrate in 24mL of methanol; the ligand solution is a 2-methylimidazole methanol solution, which is prepared by dissolving 1.64g of 2-methylimidazole in 40mL of methanol.
[0072] The adsorbent material obtained in this embodiment is coated with ZIF-67 nanoparticles, which have a water contact angle of <10° and are superhydrophilic. It showed a significant growth inhibition effect after being co-cultured with *Nyctaginosa* for 5 days. The combined effect of the phosphatamide groups and the sponge matrix increased its adsorption capacity by more than 150% at a pH close to that of seawater. After 5 cycles of adsorption and desorption, the adsorption capacity can be maintained at more than 100 mg / g.
[0073] Example 8
[0074] This embodiment is basically the same as the method in Embodiment 1, except that the MOF precursor solution is replaced. In this embodiment, the MOF precursor solution is a central metal ion solution, which is prepared by dissolving 0.14 g of copper nitrate in 10 mL of N,N-dimethylformamide; the ligand solution is prepared by dissolving 0.084 g of trimesic acid in 10 mL of N,N-dimethylformamide.
[0075] The adsorbent material obtained in this embodiment is coated with HKUST nanoparticles, with a water contact angle of <10°, exhibiting superhydrophilicity. It showed a strong growth-inhibiting effect after being co-cultured with *Nyctaginosa* for 3 days. The combined effect of the phosphate amide groups and the sponge matrix enabled it to increase its adsorption capacity by more than 110% at pH close to seawater.
[0076] As described above, although the invention has been shown and described with reference to specific preferred embodiments, it should not be construed as limiting the invention itself. Various changes in form and detail may be made without departing from the spirit and scope of the invention as defined in the appended claims.
Claims
1. A method for preparing a highly hydrophilic and antifouling MOF sponge-type uranium extraction adsorbent, characterized in that, Includes the following steps: Step 1: Select melamine sponge or polyurethane sponge as the sponge matrix, clean and dry it before use; Step 2: Prepare the phosphate-amide functionalized sponge matrix. The specific steps are as follows: Phytic acid was added to chitosan acetate solution and mixed evenly to obtain a mixed solution; the cleaned and dried sponge matrix was immersed in the mixed solution to completely wet the sponge matrix; glutaraldehyde was then added to the mixed solution, and after reacting for a period of time, the sponge matrix was removed, washed, and freeze-dried to obtain a phosphate-amide functionalized sponge matrix. In the chitosan acetate solution, the mass concentration of chitosan is 0.5-2%; the mass ratio of phytic acid to chitosan is 1:(0.5-2). Step 3: Prepare highly hydrophilic and antifouling MOF sponge uranium extraction adsorbent material. The specific operations are as follows: MOF precursor solutions, central metal ion solution, and ligand solution were prepared separately. The phosphate-amide functionalized sponge matrix was immersed in the central metal ion solution and completely wetted. The matrix was then stirred at room temperature for a period of time. The ligand solution was then added to the central metal ion solution and stirred for a period of time. After removing the sponge matrix, cleaning and drying were performed to obtain a highly hydrophilic and antifouling MOF sponge uranium extraction adsorption material. In the MOF precursor solution, the central metal ion solution is a zinc nitrate-methanol solution, and the ligand solution is a 2-methylimidazolium methanol solution. Alternatively, the central metal ion solution is a cobalt nitrate-methanol solution, and the ligand solution is a 2-methylimidazolium methanol solution; Alternatively, the central metal ion solution may be prepared with copper nitrate as the solute and N,N-dimethylformamide as the solvent; or the ligand solution may be prepared with pyromellitic acid as the solute and N,N-dimethylformamide as the solvent.
2. The preparation method of the highly hydrophilic-antifouling MOFs sponge uranium extraction adsorbent material according to claim 1, characterized in that, In step one, the cleaning conditions are: cleaning with deionized water and anhydrous ethanol two to three times in sequence; the drying conditions are: drying at 60°C.
3. The preparation method of the highly hydrophilic-antifouling MOFs sponge uranium extraction adsorbent material according to claim 1, characterized in that, Step 2: Prepare the phosphate-amide functionalized sponge matrix. The specific steps are as follows: In step (1), phytic acid is added to the chitosan acetate solution and mixed evenly to obtain a mixed solution; Step (2): Immerse the cleaned and dried sponge substrate in the mixed solution in step (1), and squeeze-release cycle 3-5 times to completely wet the sponge; Step (3): After the sponge matrix is completely wetted, glutaraldehyde is added to the mixed solution. The mass concentration of glutaraldehyde in the mixed solution is 1.5-3%. The reaction is carried out at 60℃ for 4-6 h. The sponge is taken out and washed three times with deionized water and then freeze-dried for 48 h to obtain the phosphate-amide functionalized sponge matrix.
4. The preparation method of the highly hydrophilic-antifouling MOFs sponge uranium extraction adsorbent material according to claim 1, characterized in that, In step (1), the chitosan acetate solution has a chitosan concentration of 1% and a phytic acid to chitosan mass ratio of 1:
2.
5. The preparation method of the highly hydrophilic-antifouling MOFs sponge uranium extraction adsorbent material according to claim 1, characterized in that, The specific steps for step three are as follows: Step A: Prepare the central metal ion solution and ligand solution of the MOF precursor solution respectively; Step B: Immerse the phosphate-amide functionalized sponge matrix in the central metal ion solution, and completely wet the sponge matrix by squeezing-releasing three times, and stir at room temperature for at least 30 minutes. Step C: Add the ligand solution to the central metal ion solution and stir the reaction at 25-150℃ for 3-12 hours. Step D: Remove the sponge substrate, wash it 3-5 times with deionized water and anhydrous ethanol respectively, and dry it at 60-100°C for 12 hours to obtain a highly hydrophilic and antifouling MOF sponge uranium extraction adsorption material.
6. The preparation method of the highly hydrophilic-antifouling MOFs sponge uranium extraction adsorbent material according to claim 5, characterized in that, In the MOF precursor solution: the central metal ion solution is a zinc nitrate-methanol solution, prepared by dissolving 1.19 g of zinc nitrate in 24 mL of methanol; the ligand solution is a 2-methylimidazole methanol solution, prepared by dissolving 1.64 g of 2-methylimidazole in 40 mL of methanol.
7. The preparation method of the highly hydrophilic-antifouling MOFs sponge uranium extraction adsorbent material according to claim 5, characterized in that, In the MOF precursor solution: the central metal ion solution is a cobalt nitrate-methanol solution, prepared by dissolving 1.16 g of cobalt nitrate in 24 mL of methanol; the ligand solution is a 2-methylimidazole methanol solution, prepared by dissolving 1.64 g of 2-methylimidazole in 40 mL of methanol.
8. The preparation method of the highly hydrophilic-antifouling MOFs sponge uranium extraction adsorbent material according to claim 5, characterized in that, In the MOF precursor solution: the central metal ion solution, the solute is copper nitrate, and the solvent is N,N-dimethylformamide, prepared by dissolving 0.14 g of copper nitrate in 10 mL of N,N-dimethylformamide; the ligand solution, the solute is trimesic acid, and the solvent is N,N-dimethylformamide, prepared by dissolving 0.084 g of trimesic acid in 10 mL of N,N-dimethylformamide.
9. The adsorbent material prepared by the preparation method of the highly hydrophilic-antifouling MOFs sponge uranium extraction adsorbent material according to any one of claims 1-8.
